TAX AUDIT GUNA MENDETEKSI KETIDAKPATUHAN WAJIB PAJAK AKIBAT SELF ASSESSMENT SYSTEM - INDRAYANI, THEA (: 2303-1719)
This paper aims to discuss the tax audit of taxpayers to detect non-compliance due to self-assessment system. Indonesia with a system of self assessment tax system causes the taxpayer has the opportunity to not deposit and tax reporting in accordance with actual conditions. This is caused by the behavior to avoid paying higher taxes in the amount. On the Director General of Taxation, the application of self-assessment system must be done because it brings the tax administration cost savings, but also the taxpayer non-compliance should be minimized because the harm. Director General of Taxes may make efforts to detect the presence of a tax audit of non-compliance arising as a result of payment of tax evasion.